Child poverty : aspiring to survive - Treanor, Morag (Policy Press, 2020)
Placing children's experiences, needs and concerns at the centre of its examination of contemporary policies and political discourses surrounding poverty in childhood, this book examines a broad range of structural, institutional and ideological factors common across developed nations and forges a radical new pathway for the future.